Hubungan Stres Kerja dan Cedera Otot dengan Produktivitas Tenaga Kerja pada Industri Tahu - Sri Rahayuningsih (Industrial Engineering, Engineering of Faculty, Universitas Kadiri, 2020)
In the activities of the tofu industry will be associated with muscle injury and work stress on labor productivity. In this case needed a way to find out how big the relationship between work stress with work productivity and muscle injury with worker productivity in the tofu industry. Research conducted with the population is tofu industry in Kediri Regency using non-probability sampling with purposive sampling technique. From this sample, 17 respondents were identified as having experienced work stress and injuries due to ordering excess tofu with duration <14 days and age of workers> 20 years to <80 years. Distributing questionnaires to respondents was then carried out the relationship test that is Chi-Square Test. From these tests the results obtained in accordance with the hypothesis on work stress have a relationship with productivity that is worth Asymp. The work stress variable of 0,000 has reached the value of 0,000 <0.05 and the productivity variable is 0.002 <0.05. Whereas in muscle injury with work productivity Asymp value. The work stress variable of 0,000 has reached the value of 0,000 <0.05 and the productivity variable is 0.002 <0.05 Didalam kegiatan industri tahu akan berkaitan dengan cedera otot dan stress kerja terhadap produktivitas tenaga kerjanya. Dalam hal ini diperlukan cara untuk mengetahui seberapa besar hubungan pada stress kerja dengan produktivitas kerja dan cedera otot dengan produktivitas pekerja pada industri tahu tersebut. Dilakukan penelitian dengan populasi adalah industri tahu di Kabupaten Kediri menggunakan non-probability sampling dengan teknik purposive sampling. Dari sampel tersebut didapatkan responden sejumlah 17 orang dengan kriteria pernah mengalami stress kerja dan cedera akibat pemesanan tahu yang berlebih dengan durasi < 14 hari dan usia pekerja >20 tahun sampai < 80 tahun. Dilakukan penyebaran kuisioner kepada responden kemudian dilakukan uji hubungan yaitu Uji Chi-Square. Dari uji tersebut didapatkan hasil sesuai dengan hipotesis pada stress kerja memiliki hubungan dengan produktivitas yang bernilai Asymp. Sig variabel stress kerja sebesar 0,000 sudah mencapai nilai 0,000 < 0,05 dan variabel produktivitas sebesar 0,002 < 0,05. Sedangkan pada cedera otot dengan produktivitas kerja nilai Asymp. Sig variabel stress kerja sebesar 0,000 sudah mencapai nilai 0,000 < 0,05 dan variabel produktivitas sebesar 0,002 < 0,05.